MODEL PELAKSANAAN PRAKTIK KERJA INDUSTRI PADA SEKOLAH MENENGAH KEJURUAN (SMK) YANG BERORIENTASI PADA PENYIAPAN SISWA UNTUK MENJADI TECHNOPRENEUR - Sunyoto Sunyoto; Muhammad Khumaedi; Agus Suharmanto (Universitas Negeri Semarang, 2015)
The purpose of this study is to find a model of the implementation of the Industrial Employment Practices (Prakerin) oriented to prepare for the birth of technopreneur. These are multi penelitiaan years, which is designed in two years using the approach of Research and Development (R D). The focus of research is high vocational school (SMK) Muhammadiyah Salatiga, program of Engineering (TP) and Vehicle Engineerin (TKR). The small medium enterprices (SME) as place of practices place is owned entrepreneurs in Salatiga City and surrounding areas. Data were collected through interviews, questionnaires, observation, and documentation. Analysis of the data through qualitative and quantitative approaches. The results of the first year of the study include 1) has been successfully recorded as many as 176 students (82.24 %) of 214 first graders who are interested to become entrepreneurs, which includes 93 TP students and 83 TKR students; 2) has been successfully recorded as many as 50 SME, covering 33 areas of TP and 27 TKR; 3) Have produced models of implementation-oriented Prakerin preparing students to become entrepreneurs or technopreneurs. Suggestions put forward related to the first year of this research is that this model can actually be implemented in the second year, so that these models can be known effectiveness.